Estudio comparativo del Rendimiento Académico de los Estudiantes de primer semestre de la carrera de Pedagogía de las Ciencias Experimentales periodo octubre 2017- marzo 2018 - Paltàn Malàn, Freddy Manuel (2018)
In public universities, the presence of students with medium and low socioeconomic requirements with the difficulties of their social status that are still increasing, result in phenomena such as Academic Performance, student desertion, among others. The present research work whose subject is: Comparative Study of the Academic Performance of the students of the first semester of the Pedagogy Career of the Experimental Sciences period October 2017- March 2018, has as objective to determine the Academic Performance of the students of the first semester of said race. The population was 70 students of Mathematics and Physics, Biology and Chemistry and Computer Science, data collection with direct observation, which were processed statistically with the Microsoft Excel 2016 tool, with descriptive statistics techniques. As a result we could find the differences in the Academic Performance of the students, being the Career of Pedagogy of the Experimental Sciences: Mathematics and Physics that in the global (considering the three components of evaluation) if it places in the first place, in addition; A brief analysis by sex, the book determine that women, who have a slightly higher Academic Performance compared to males, in all components studied. It is important to take these differences into account so that future problems that affect students throughout their professional training can be avoided in this way.